O aletycznej naturze wiedzy - Palczewski, Rafał (Filozofia Nauki, 2015)
The paper is devoted to the alethic nature of knowledge, represented in the trad-itional epistemology by the truth condition (as a part of the so-called JTB definition of knowledge): one can only know what is true. The main motivation behind the art-icle is to show that, despite the recent criticism, the truth condition is adequate and well-justified from the linguistic point of view. I discuss two general types of objec-tions: one from the epistemological paradoxes (the Knower Paradox, the Knowability Paradox, and the Skeptic Paradox) and one from the would-be non factive uses of “to know”. The “paradoxical” path leads some authors (Grobler, Woleński) to a simple negation or to a more subtle restriction or modification of the truth condition. The “ordinary language” path leads other authors (Hazlett) to the thesis that the truth condition cannot be based on factivity of “to know”. I argue that both of these approaches are problematic, mainly because they are not well supported. In addition, I try to show that “to know” is factive in Stalnaker’s sense: a sentence of the form “s knows that p” both entails and pragmatically presupposes the truth of “p”. I treat this as the major premise in the argument for the alethic nature of knowledge.